DEVELOPING DISGAME: A ROBLOX-BASED EDUCATIONAL GAME FOR YOUNG LEARNERS' LISTENING COMPREHENSION - Rafli Muhamad Ridhwan; Lucky Rahayu Nurjamin; Irsyad Nugraha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Listening comprehension is an essential skill in English language learning because it provides learners with the linguistic input necessary for language acquisition. However, young learners often experience difficulties in understanding spoken English due to limited exposure to authentic language input and a lack of engaging listening activities. This study aimed to develop DISGAME (Diajar Inggris Sabari Ngagame), a Roblox-based educational game designed to support young learners' listening comprehension through interactive, audio-based learning activities. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The game was developed using Roblox Studio and integrates Total Physical Response (TPR) principles, game-based learning, and listening-focused activities within a virtual learning environment. The findings indicate that DISGAME was successfully developed as a fully audio-based learning medium in which learners are required to respond physically to spoken instructions across four progressively structured stages encompassing vocabulary recognition, greetings, direction-following, and spelling. Roblox proved to function not only as a gaming platform but also as an immersive, interactive learning environment that supported active engagement with spoken English. The study concludes that DISGAME has the potential to serve as an alternative learning medium for supporting young learners' listening comprehension in the English as a Foreign Language (EFL) context. ABSTRAK Listening comprehension merupakan keterampilan penting dalam pembelajaran bahasa Inggris karena menyediakan masukan bahasa yang diperlukan bagi proses pemerolehan bahasa. Namun, young learners sering mengalami kesulitan memahami bahasa Inggris lisan akibat keterbatasan paparan terhadap authentic language input dan minimnya aktivitas menyimak yang menarik. Penelitian ini bertujuan mengembangkan DISGAME (Diajar Inggris Sabari Ngagame), permainan edukatif berbasis Roblox yang dirancang untuk mendukung listening comprehension pada young learners melalui aktivitas pembelajaran interaktif berbasis audio. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE, meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Permainan dikembangkan menggunakan Roblox Studio dengan mengintegrasikan prinsip Total Physical Response (TPR), pembelajaran berbasis permainan, dan aktivitas menyimak dalam lingkungan belajar virtual. Hasil penelitian menunjukkan bahwa DISGAME berhasil dikembangkan sebagai media pembelajaran yang sepenuhnya berbasis audio, di mana pembelajar diminta merespons instruksi lisan melalui tindakan fisik dalam empat tahap permainan yang meningkat secara bertahap, mencakup pengenalan kosakata, sapaan, mengikuti arah, dan ejaan. Roblox terbukti berfungsi tidak hanya sebagai platform permainan, tetapi juga sebagai lingkungan belajar yang imersif dan interaktif. Penelitian ini menyimpulkan bahwa DISGAME berpotensi menjadi media pembelajaran alternatif untuk mendukung listening comprehension young learners dalam konteks English as a Foreign Language (EFL).